Penguatan Moda Transportasi Lokal dalam Mendukung Kabupaten Pulau Morotai Sebagai Destinasi Wisata Unggulan - Ilham Junaid (Department of Urban and Regional Planning, Diponegoro University, 2019)
The Ministry of Tourism of the Republic of Indonesia has chosen Morotai Island Regency as one of ten prioritized tourism destinations. This policy requires tourism supporting elements including an adequate transportation system. This research aims to identify the supporting capacity of the local transportation modes from which the strategies of tourism development derived from. A qualitative methodology is applied by using naturalistic and interpretative approaches to investigate the capacity of transportation modes in Morotai Island. Interviews with the local tourism agency officials and the local transportation service providers are completed for collecting relevant data and information. The research reveals that the existing transportation modes can support tourism development in Morotai. However, there are some attempts required to support tourism based transportation system: strengthening the synergetic relations between the local government and the air transportation service providers for increasing flight schedule for tourists; providing creative local based transportation modes to support better tourism development; and providing accurate information about sea transportation service to support Morotai as the prioritized tourism destination.